Perception of fatness - Jałkiewicz, Małgorzata (Anthropological Review, 1997)
The study’s objective was to find out whether there is a relationship between bodily fatness traits described with anthropometric measurements and the assessment of the physical attractiveness of people with different degree of fat deposition. Furthermore, an attempt was made to answer the question whether we perceive the physique of another man as a whole or if we pay more attention to certain parts of the body and whether there is a stereotype of desirable fat deposition.